Nanoemulsion of Lavandula angustifolia Essential Oil/Gold Nanoparticles: Antibacterial Effect against Multidrug-Resistant Wound-Causing Bacteria - Balqis A. Fadel; Bassma H. Elwakil; Esraa E. Fawzy; Marwa M. Shaaban; Zakia A. Olama (Molecules, 2023)
Hospitalized patients are severely impacted by delayed wound healing. Recently, there has been a growing focus on enhancing wound healing using suitable dressings. Lavandula angustifolia essential oil (LEO) showed potential antibacterial, anti-inflammatory, and wound healing properties. However, the prepared gold nanoparticles possessed multifunctional properties. Consequently, the present investigation aimed to synthesize a novel nanosystem consisting of nano-Lavandula angustifolia essential oil and gold nanoparticles prepared through ultrasonic nanoemulsifying techniques in order to promote wound healing and combat bacterial infection. LEO showed potent antibacterial activity against Klebsiella pneumoniae, MRSA and Staphylococcus aureus with minimum inhibitory concentration (MIC) values of 32, 16 and 16 µg/mL, respectively, while exhibiting low activity against Proteus mirabilis. Interestingly, the newly formulated nano-gold/nano-Lavandula angustifolia penetrated the preformed P. mirabilis biofilm with a full eradication of the microbial cells, with MIC and MBEC (minimal biofilm eradication concentration) values reaching 8 and 16 µg/mL, respectively. The cytotoxic effect of the novel nanoformula was also assessed against WI-38 fibroblasts vero (normal) cells (IC50 = 0.089 mg/mL) while nano-gold and nano-Lavandula angustifolia showed higher results (IC50 = 0.529, and 0.209 mg/mL, respectively). Nano-gold/nano-Lavandula angustifolia formula possessed a powerful wound healing efficacy with a 96.78% wound closure. These findings revealed that nano-gold/nano-Lavandula angustifolia nanoemulsion can inhibit bacterial growth and accelerate the wound healing rate.